The Use of Glass-Fibre Reinforced Plastic on the Northern Sewerage Project Stage 1 – Design and Construction Considerations - S Goff (The Australasian Institute of Mining and Metallurgy, 2011)
The Northern Sewerage Project (NSP) is a $650 M infrastructure project that will increase the capacity of the sewerage system for Melbourne’s growing northern suburbs while also helping to protect the Merri and Moonee Ponds creeks by significantly reducing the number of sewage overflows that can occur after heavy rainfall. The NSP consists of two stages: Stage 1 (NSP1) will be owned and operated by Melbourne Water Corporation, and Stage 2 (NSP2) will be owned by Yarra Valley Water and operated by Melbourne Water Corporation.Glass-fibre reinforced plastic (GRP) was used on both NSP stages, however, since Stage 1’s schedule for installation of GRP was slightly ahead of Stage 2’s, this paper will only focus on Stage 1’s use of GRP.NSP1 involves the construction of 7.9 km of new sewer tunnel ranging in diameter from 1.6 to 2.5 m, five main access shafts at depths of up to 65 m, and connections to the existing sewerage system including several access manholes. Construction began in 2007, and project completion is expected in 2012.The original design for NSP1 specified the use of high-density polyethylene (HDPE-) line precast concrete pipes as the final tunnel lining and HDPE-lined reinforced concrete for the access shafts and manholes. During construction, the rising cost of precast concrete pipes and the introduction of an additional GRP pipe supplier in the market justified a review of the tunnel final lining material. The contractor-proposed GRP pipe alternative was accepted for the final tunnel lining based on time and cost savings that were possible without compromising the design intent. After gaining experience with GRP through this design change, Melbourne Water Corporation reviewed and accepted GRP as the final lining for five smaller connection manholes. The use of GRP for the manholes was particularly inventive as the redesign made use of the approved tunnel GRP pipes as both a structural and corrosion-resistant lining.This paper discusses the use of GRP on NSP1; how the change in material, from concrete to GRP, affected the design philosophies assumed during detailed design; and how construction methods were modified to handle the less rigid GRP material. Details on the structural, hydraulic and durability considerations for the design are included, as are details about the time and cost savings and the quality and safety improvements that were achieved during construction.